2006
DOI: 10.1007/s00737-006-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Mood state and psychological adjustment to pregnancy

Abstract: The aim of this study was to investigate whether there is an association between antenatal mood state (depression and anxiety) and psychological adjustment to pregnancy. Participants were first-time, low obstetric risk mothers at a Sydney teaching hospital who completed self-report questionnaires measuring depression, anxiety, thoughts about motherhood and self as mother and relationship with the fetus. Higher symptom levels of antenatal anxiety were related to less optimal maternal-fetal quality of attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
116
3
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 55 publications
9
116
3
17
Order By: Relevance
“…Literatürde bildirilen gebelik dönemi depresyon sıklığı ile ilgili yurt dışı [14][15][16][17][18][19] ve yurt içi [20][21][22][23][24][25] Çalışma bulgularıyla benzer şekilde; yaşayan çocuk sayısının [43] gebeliğin istenme durumunun [21,36,39], önceki gebeliklerinde kayıp yaşamış olmanın [21], gebelik döneminde sorun yaşamanın [22] ve cinsiyet beklentisinin [21,39] gebelikte depresyon düzeyini etkilemediği gösterilmiştir. Karataylı [10] ile Şahin ve Kılıçaslan'ın [13] çalışmalarındaki bulgularla paralel olacak şekilde gebe olduklarını öğrenince olumlu duygulanım yaşayan kadınlarda depresyon düzeyinin daha düşük, gebeliklerini öğrendiklerinde ve üçüncü trimesterde korku, endişe, tedirginlik, üzüntü gibi olumsuz duygular yaşayanların ise depresyon düzeyinin yüksek olduğu görülmüştür.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Literatürde bildirilen gebelik dönemi depresyon sıklığı ile ilgili yurt dışı [14][15][16][17][18][19] ve yurt içi [20][21][22][23][24][25] Çalışma bulgularıyla benzer şekilde; yaşayan çocuk sayısının [43] gebeliğin istenme durumunun [21,36,39], önceki gebeliklerinde kayıp yaşamış olmanın [21], gebelik döneminde sorun yaşamanın [22] ve cinsiyet beklentisinin [21,39] gebelikte depresyon düzeyini etkilemediği gösterilmiştir. Karataylı [10] ile Şahin ve Kılıçaslan'ın [13] çalışmalarındaki bulgularla paralel olacak şekilde gebe olduklarını öğrenince olumlu duygulanım yaşayan kadınlarda depresyon düzeyinin daha düşük, gebeliklerini öğrendiklerinde ve üçüncü trimesterde korku, endişe, tedirginlik, üzüntü gibi olumsuz duygular yaşayanların ise depresyon düzeyinin yüksek olduğu görülmüştür.…”
Section: Discussionunclassified
“…Çalışma sonuçlarını destekler nitelikteki bazı araştırmalarda; kadınların primigravida ve multigravida olma durumlarına göre doğum öncesi anksiyete düzeyleri arasında fark olmadığı [40,43,45], gebeliğini planlamamış olanların anksiyete ortalamalarının genel ortalamadan farklı çıkmadığı [12,40,43], gebeliği isteme ve doğacak bebeğin cinsiyetini bilme [3,39] ve düşük yapma [21], gebe olduğunu öğrenince sevinme durumu [13] ile anksiyete puanları arasında ilişki olmadığı sonuçları elde edilmiştir. Araştırmada ulaşılan bu sonuçlar ve destekleyen çalışmalar genelde her gebe kadının gebelik ve doğuma ilişkin kaygı yaşadığını göstermektedir.…”
Section: Discussionunclassified
“…With spirit possession attribution however, sadness clustered with irritability and interpersonal conflict, particularly with partners. Studies show conflicts with intimate partners can both be a result of perinatal depression (Kazi et al, 2006;Hart et al, 2006), and a risk factor for perinatal depression across diverse cultural settings (Farber et al, 1996;Bolton et al, 1998;Pajulo et al, 2001). In the context of low socio-economic status and multifocal family structures, the need to foster supportive networks is perhaps greater.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 6% of women suffer from phobic FOC (tokophobia), which is often related to previous labor trauma (Butcher, 2014;Gosselin et al, 2016). To a varying extent, the following factors are considered to be predictors of FOC during pregnancy: previous life experience, hearing negative stories about labor, posttraumatic stress disorder (caused by rape, abuse, or a previous complicated labor), lack of childbirth experience, ambivalence towards pregnancy and maternity (Hart, McMahon, 2006), age, education, social-economic status, and lack of social support (Laursen et al, 2008;Räisänen et al, 2014). Other studies have indicated significant psychological predictors for FOC, for instance, personality type, anxiety, and low self-esteem (Ryding et al, 2007;Handelzalts et al, 2015;Klabbers et al, 2016), and psycho-social FOC predictors (Toohill et al, 2014).…”
Section: Introductionmentioning
confidence: 99%